Ulcus vulvae acutum. - Merico, G. (European Journal of Pediatric Dermatology, 2014)
Ulcus vulvae acutum is an acute, painful, non-venereal ulceration, that often occurs in young girls before they start sexual activity (1, 2) and is associated with symptoms of flu-like fever: the ulcer is unique, sometimes two or more rarely multiple ulcers are evident; the ulcer has a deep bottom covered by sanious exudate or eschars or blackish crusts; it heals spontaneously with scar within a few weeks. It has been described for the first time by Lipschutz (5) in an adolescent and related with numerous infectious factors such as Mycoplasma (4), paratyphoid fever (6), influenza (9) and especially infectious mononucleosis (3, 8). Some Authors isolated EBV from ulcerative lesions (7), but it is believed that the disease is more expression of a reactive process than of a direct infection. EBV can be transmitted by oral-genital or genital-genital contagion, but given the onset even before the onset of sexual activity, it is more likely that the infection does not occur by sexual contact. For the etiologic diagnosis it is best to seek IgM antibodies against EBV capsidic antigens appearing earlier than those directed against nuclear antigens.